If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z = (2 + i)(2 + i) Multiply (2 + i) * (2 + i) z = (2(2 + i) + i(2 + i)) z = ((2 * 2 + i * 2) + i(2 + i)) z = ((4 + 2i) + i(2 + i)) z = (4 + 2i + (2 * i + i * i)) z = (4 + 2i + (2i + i2)) Combine like terms: 2i + 2i = 4i z = (4 + 4i + i2) Solving z = 4 + 4i + i2 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Simplifying z = 4 + 4i + i2
| -x-104=11x+136 | | 140/÷7/15 | | 2b-3b=-26 | | 33x+1=x+5 | | z=(2+i)(2+1) | | 3x-30+x-10+3x=360 | | W/-3.4=-25.5 | | 2(5+x)=6+3x | | 32x-28=-92 | | =2-6x+9 | | z=(2+i)2 | | (5/(2u))-(3/(7u))=1 | | .3333333333333333333333333333333333(6x+12)-2(x-7)=19 | | 5(3-2y)=3 | | 3-x-5=10 | | 2x-0.64x= | | 6y^2/y | | .3333333333333333333333333333333333(6x-12)-2(x-7)=19 | | 3x-5=11x-29whatisx | | .33(6x-12)-2(x-7)=19 | | 5x+4(6x-13)=93 | | -5F(3F+6)(9-2F)=0 | | -2-5x=2x+68 | | log(3x)=1.75 | | -2*v/2=-6 | | 2x+17=12x-103whatisx | | 24y=890y | | -2(x-4)-5=23 | | 9x-6+6x-1=98 | | (6x-7y)(6x-7y)(6x-7y)+(8x+y)(x+8y)(4x-4y)= | | -7x-(9+2x)=-45 | | 9(4+2c)-10=8c+106 |